Multimodal transport - risk and environment - Ștefаnov, O; Аgаpe, А. G; Nita, C. M; Bocanete, P; Jalan, V (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
The risks of multimodal transport depend on both stochastic parameters - application of the probability calculation to the results obtained by statistics, and uncertain parameters - difficult to determine. The use of a mathematical model requires a careful analysis of all the risks assigned to the multimodal transport chain, possible overload options and the consideration of the whole spectrum of control activities. The mathematical model must be able to sustain changes over time at a certain stage in order to provide options for reducing the overall risk, to capitalize on it, in particular when choosing other routes and types of transport.